Innovative education training program of hajj healthcare workers improves the outcomes of Indonesian elderly hajj pilgrims - Probosuseno, Probosuseno; Fidiansjah, Fidiansjah; Rochmah, Wasilah; Mukti, Ali Ghufron (Universitas Negeri Yogyakarta, 2022)
The ability of the Muslim community in Indonesia to perform the hajj pilgrimage as the completion of the fifth pillar of Islam is increasing. With the increase in life expectancy, the number of Indonesian elderly hajj pilgrims (EHP) are consequently growing. This leads to an increase in morbidity and mortality in EHP due to chronic conditions such as impairments, disabilities, and diseases. Thus, an innovative training program that contains practical tips for a healthy hajj experience, especially for the elderly is needed in order to improve the healthcare service to the elderly pilgrims. This study aims to investigate the effect of innovative training on the performance of Hajj Healthcare Workers of Indonesia (HHWI) and on the clinical outcomes of elderly hajj pilgrims. This is a quasi-experimental study. The population of this study was all HHWI from the Surakarta embarkation in 2014. The sample of this study was all 21 HHWI from Yogyakarta, who received innovative training consisting of EHP special care training (theory and practice) in addition to basic national training. Twenty-one HHWI from Surakarta were randomly chosen as control group and only received basic national training. Pre and post-tests were used to assess knowledge of HHWI after training. The average pretest scores of the intervention and control groups were 48.50 and 48.07, respectively (p=0.337), while the post-test score the of the intervention group was 86.83 (p = 0.033). The measured parameters were the performance of HHWI which is reflected by EHP mortality rate, the number of outpatients, and the number of patients referred to the outpatients. We included the EHP under the supervision of HHWI, which has acquired training. EHP morbidity was evaluated as number of outpatients and referred patient. There are 2216 outpatients from the intervention group as compared with 2144 in control group, with most of the are 60-70 years old (p= 0,075). The number of referred EHP in intervention and control groups were 10 and 30 patients, respectively (OR 2.94; p= 0.002). As for the mortality cases, we observed 7 EPH death during the hajj period (2 EPH from intervention group vs 5 EPH from control group; OR 0.263; p=0.207). Innovative training could reduce referral morbidity and mortality in elderly hajj pilgrims.